The Role of Faith and Moral Education in Generation Z and Generation Alpha to Welcome the Golden Indonesia 2045 - Addarunnafis, Muhammad; Rabbani, Syarifah Aulia (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The great vision of the Indonesian nation is towards the Golden Indonesia 2045. To establish this vision, it is necessary to have moral education as a basic capital for Generation Z and Generation Alpha as an internal fortress in facing challenges in the future. However, many moral decline behaviors continue to be shown by Generation Z and Generation Alpha, even though this generation is the hope of the Indonesian nation in the future. So the purpose of this study is to the role of moral education in Generation Z and Generation Alpha in welcoming the golden Indonesia 2045. The research method used is Library Research with a descriptive approach. The results of the study show that moral education is the key as part of the moral values ​​of religious-Pancasilaism to the two generations. Because through faith (nature) moral education (nurture) is born as an internal and external factor in humans to filter bad influences that come from within or from outside. The future of Indonesia is at stake because it is in the hands of Generation Z and Generation Alpha. Therefore, through the synergy of multi-connected projections of positive trends in faith and moral education in the family environment, educational environment, and social community environment as a manifestation and embodiment of nature and nurture from the cradle to the present and the future, it can shape generation Z and generation Alpha into a religious-Pancasilaist generation as a great capital to lead the Indonesian nation in the future.   Keywords: Faith and Morals, Generation Z, Generation Alpha